Peran Gaya Kepemimpinan, Budaya Organisasi dan Reward Terhadap Komitmen Kerja Karyawan - Lilik Kustiani; Diah Widiawati; Kurnia Isnuwardiati (Department of Management FEB Unhas, 2021)
Employees who have a high commitment, have a desire to defend themselves as members of the organization. Therefore, to develop an organization, various aspects must be considered that can create work commitment. This study aims to examine: 1) the influence of leadership style on work commitment, 2) the influence of organizational culture on work commitment and 3) the effect of reward on work commitment. This research is a quantitative descriptive study using multiple regression analysis. The population in this study was all employees at KOPPAS